PENGARUH GAYA KEPEMIMPINAN BERMOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN GERUNGGANG KOTA PANGKALPINANG - Dinda Maharani; Rindu Nendy (Universitas Muhammadiyah Metro Lampung, 2019)
The regional goverment is a public organization whose role is increasingly important in social development and services. The purpose of this study is to analyze and determine the magnitude of offects that leadership style and motivation (independent variables) have on the employee performance (dependent variable) in the district office of Sungailiat, Bangka Regency, and to determine which independent variabel has the most effect on the dependent variabel.This is a quantitative research with survey approach and a sample of 30 employees using cencus as sampling technique. In this study, the independent variables consist of leadership style and motivation while the dependent variable is employee performance. The instrument testing uses validity test and reability test. The data analysis method uses multiple linear regression with t test and F test. The result suggested that the two independent variables significantly affect amployee performance. This is shown in F test wherein the F count (9.493) > F table (3,33), while the significance rate was (0.001) < alpha at the rate of 5% or 0.05. Ha is accepted and Ho was rejected. The coefficent of determinant Adjusted R Square was 0.369 or 36.9%, hence the simultaneous effect of X on Y is 36.3%. It is found in the t test that the t count 2.63 > t table 2.045 in XI, and in X2 the t count is 2.492 > t table 2.045. Therefore, it can be comcluded that the independent variables (X) have significant effects on the dependent variable (Y), either simultaneousy or individually. Keyword : Leadership Style, Motivation, and Employee Performance